The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/pcn.12944
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral tryptophan, serotonin, kynurenine, and their metabolites in major depression: A case–control study

Abstract: Aim Tryptophan is the sole precursor of both peripherally and centrally produced serotonin and kynurenine. In depressed patients, tryptophan, serotonin, kynurenine, and their metabolite levels remain unclear. Therefore, peripheral tryptophan and metabolites of serotonin and kynurenine were investigated extensively in 173 patients suffering from a current major depressive episode (MDE) and compared to 214 healthy controls (HC). Methods Fasting plasma levels of 11 peripheral metabolites were quantified: tryptoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 49 publications
8
31
1
2
Order By: Relevance
“…Higher levels of IL-1β can also upregulate TKP (reviewed in Maes et al, 2011), so this may have contributed to the current findings. Maternal postpartum FLX decreased plasma XA concentration, which is consistent with data in individuals with MDD (Colle et al, 2020). XA has not been specifically described as either neuroprotective or neurotoxic, but its downstream effects on the glutaminergic system have been implicated in psychiatric diseases (reviewed Fazio et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Higher levels of IL-1β can also upregulate TKP (reviewed in Maes et al, 2011), so this may have contributed to the current findings. Maternal postpartum FLX decreased plasma XA concentration, which is consistent with data in individuals with MDD (Colle et al, 2020). XA has not been specifically described as either neuroprotective or neurotoxic, but its downstream effects on the glutaminergic system have been implicated in psychiatric diseases (reviewed Fazio et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted February 12, 2021. ; https://doi.org/10.1101/2021.02.11.430473 doi: bioRxiv preprint concentration, which is consistent with data in individuals with MDD (Colle et al, 2020). XA has not been specifically described as either neuroprotective or neurotoxic, but its downstream effects on the glutaminergic system have been implicated in psychiatric diseases (reviewed Fazio et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, as well as clinically, decreased plasma picolinic acid levels have been demonstrated in depressed patients (Ryan et al, 2020), and picolinic acid has also been shown to produce significant antidepressant effects in a typical depression (Davidson et al, 2003). Our study demonstrated that the five phytochemicals with improved bioavailability after combination (saikogenin F, saikogenin G, albiflorin, methyl gallate, paeonimetabolin II) were significantly positively correlated with picolinic acid, a metabolite that was significantly downregulated in depressed patients (Colle et al, 2020). Besides, chronic stress can cause imbalances in the kynurenine metabolic pathway and excessively produce the "↓" or "↑" means the metabolite significantly decreased or increased in 3 h group compared with 0 h group.…”
Section: Picolinic Acidsupporting
confidence: 60%
“…Similarly, HT-IG (100.28 ± 5.35 µg/g) and TT-DV (109.29 ± 11.08 µg/g) fruits showed higher Thr contents in AZ samples compared to other states. Trp is the precursor of serotonins, which regulate human mood, anxiety, appetite, and sleep [ 49 ]. Among the analyzed samples, HT-IG and the commercial local variety (CAR) harvested from CA showed significant higher contents of Trp at 71.82 ± 1.73 µg/g and 58.82 ± 2.04 µg/g, respectively, while TT-DV fruits grown in AZ had higher levels of Trp (68.67 ± 10.75 µg/g) compared to other locations and varieties.…”
Section: Resultsmentioning
confidence: 99%